Yemen’s Houthis: Legal dilemmas in the fog of war (TEST Trento Student Law Review, 2025)
This paper examines the legal and geopolitical complexities surrounding the rise of the Houthis in Yemen’s ongoing conflict. It provides a historical overview of the group’s evolution and assesses their classification under international law. The study explores the legal implications of the Houthis' actions, particularly in relation to the principles of State sovereignty, self-defense and the use of force against non-state actors. By analyzing international legal instruments such as the United Nations Charter, Geneva Conventions, and customary international law, this paper evaluates the legitimacy of force used by and against the Houthis. Special attention is given to the classification of their attacks on maritime vessels and whether these constitute acts of piracy or lawful engagements within a Non-International Armed Conflict (NIAC). The paper further investigates the role of key stakeholders, including Saudi Arabia and the United States in responding to Houthi actions and the broader implications for international security. Through a doctrinal legal research approach, supported by case law and scholarly analysis, the study provides insights into the evolving challenges of addressing non-state actors within the framework of international law. Ultimately, this paper aims to contribute to the ongoing discourse on state sovereignty, collective security, and the legal boundaries of self-defense in contemporary armed conflicts.
Keywords: Yemen; Houthis; Non-State Actors; Armed Conflict; Humanitarian Law